The Effect of a Mediator on Scaffolding EFL Student Teachers’ Teaching Competencies, Self- Efficacy and Self–Awareness (Journal of the College of Education for Women, 2019)
This study aims to find out the effect of the mediator on scaffolding fourth yearstudent- teachers' teaching competencies and their self-efficacy. The present study combines scaffolding and self-efficacy by using a mediator on scaffolding students affects teaching competencies and selfefficacy and from the results of which the existence of student-teachers’ selfawareness was ensured as an effect of the same independent variable. The model affects their teaching competencies and led them to be aware of the needs of their pupils and themselves.